The impact of artificial intelligence on the development of electronic financial services - AL-Habashneh, Amjad Ghazi; Al-Daoud, Khaleel Ibrahim; Oraini, Badrea Al; Mohammad, Suleiman Ibrahim Shelash; Vasudevan, Asokan; Al-Habashneh, Omar Amjad; Xia, Lian (Growing Science, 2025)
The study aimed to examine the impact of artificial intelligence on the development of electronic financial services. The population of the study involves employees from Jordanian commercial banks distributed across branches and the general administration. The researcher used a survey as the study instrument to collect data from the study sample, with 356 surveys distributed via a link. The Statistical Package for the Social Sciences (SPSS) was used to analyze the data. The results showed an impact of using artificial intelligence on the development of electronic financial services in Jordanian commercial banks. One of the prominent recommendations was for the management of commercial banks to keep pace with the advancements and developments in artificial intelligence and the expert systems environment by providing advanced operating and storage systems to keep up with the developments in electronic financial services.